(untitled) (Third Sector Social Economic Review, 2026)
This study analyzes physician migration from Türkiye by comparatively examining the perceptions of push factors among physicians who have migrated and those who have not. The research is based on quantitative survey data collected from 829 physicians. Push factors were measured using five-point Likert-type items, the relevant dimensions were transformed into factor scores, and differences between the two groups were tested using the non-parametric Mann–Whitney U test. The findings indicate that structural factors such as workload, wage levels, perceptions of the country’s economic future, and the social prestige of the medical profession constitute the primary push factors generating statistically significant perceptual differences between migrant and non-migrant physicians. These results demonstrate that physician migration from Türkiye is closely associated with macro-level structural conditions rather than individual career preferences. It is also evident that these conditions significantly shape migration perceptions and future expectations not only among physicians who have already migrated but also among those who continue to practice in Türkiye. The study emphasizes that policy interventions addressing physician migration should move beyond individual incentives and prioritize structural approaches aimed at reducing workload, improving working conditions, strengthening economic stability, and restoring institutional trust in the medical profession.